Ensuring Energy Security as a Condition for Sustainable Development of Poland - Jędral, Waldemar (Studia Ecologiae et Bioethicae, 2020)
Energy security is a condition for the sustainable development of Poland. The paper is aimed at discussing problems related to ensuring energy security and presenting rational ways of solving them. The author justifies the need for a significant reduction in the burning of fossil fuels, among others, to reduce the emissions of many harmful substances. The need for efficient, reliable, controllable, and stable energy sources throughout the year, and in any weather has also been highlighted. Basing Polish energy on large wind and solar farms is prevented by the lack of effective methods for storing large amounts of electricity (e.e.). An important role in this respect may be played by massive development of small, distributed RES producing e.e. and heat for personal use and sending surplus e.e. to the network. The energy efficiency potential of production, and the related operating processes, can be considered an important resource. It is also necessary to significantly reduce the wastage of large amounts of energy to produce disposable, non-repairable, or low-quality products. The method used in the paper is a critical analysis of the current situation, along with improper solutions, using simple estimates, based on information from the available literature on the subject.